Kepuasan Pelanggan Pada Industri Penyedia Layanan Mobile Internet Di Jakarta - Ariyawira Binui dan Eddy Herjanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The rapid advances in technology, especially in the mobile sector, make communication and access to information very easy. These things make the internet as one of the main needs of modern humans. Companies that move as internet service providers must be able to find out what factors influence customer satisfaction to increase sales and attract the services offered. This study aims to analyze what factors influence consumers in the mobile internet service provider industry in Jakarta. These factors include price suitability, network quality, and service quality. The data used in this study is primary data, which is the result of 150 respondents in Jakarta. This research took place from March 2018 to May 2018. The data analysis method used in this study was descriptive analysis method and multiple linear regression analysis. The results of the study show that these three variables have significant variables on the level of customer satisfaction. Where dimensions that have the most dominant influence are dimensions of network quality, then followed by quality dimensions.